Preparation and Characterization of Silk Fibroin Nanoparticles as a Potential Drug Delivery System for 5-Fluorouracil - Hamid Rahmani; Ali Fattahi; Komail Sadrjavadi; Salar Khaledian; Yalda Shokoohinia (Tabriz University of Medical Sciences, 2019)
Purpose: The aim of this study is to prepare 5-fluorouracil (5-FU) loaded silk fibroin nanoparticles (SFNPs) and to achieve a controlled release delivery system with the high loading capacity. Methods: SFNPs with 1:1, 1:3, and 1:10 ratios of 5-FU to silk fibroin were prepared. SFNPs were characterized by Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) analysis, Scanning electron microscope (SEM), and Transmission electron microscope (TEM). Loading efficiency, in vitro release, and cell viability were studied for optimal SFNPs. Results: The ratio of 1:1 was optimal formulation with the size and polydispersity index (PDI) of 221.03 nm and 0.093 before freeze drying, and 286.7 nm and 0.154 after freeze drying by lactose, respectively. The loading efficiency and loading content of this ratio were 52.32% and 34.35%, respectively. FT-IR and XRD analysis indicated the conformational change (from random coil to β-sheet) in the structure of nanoparticles by increasing amount of the drug, which caused the smaller size, the higher loading efficiency, and the slower release pattern. The drugloaded nanoparticles reached to the half maximal inhibitory concentration (IC50) that were comparable with free drug on MCF7 (human breast cancer) cell line. Conclusion: This study was planned to achieve a promising controlled release drug delivery system for carrying 5-FU, as a potent anticancer drug. SFNPs were found proper candidates for delivery of a hydrophilic drug such as 5-FU.